Mechanistic Study of Stress Relaxation in Urethane-Containing Polymer Networks - Brutman, Jacob P; Fortman, David J; De Hoe, Guilhem X; Dichtel, William R; Hillmyer, Marc A (The journal of physical chemistry. B, 2019)
Cross-linked polymers are used in many commercial products and are traditionally incapable of recycling via melt reprocessing. Recently, tough and reprocessable cross-linked polymers have been realized by incorporating cross-links that undergo associative exchange reactions, such as transesterification, at elevated temperatures. Here we investigate how cross-linked polymers containing urethane linkages relax stress under similar conditions, which enables their reprocessing. Materials based on hydroxyl-terminated star-shaped poly(ethylene oxide) and poly((±)-lactide) were cross-linked with methylene diphenyldiisocyanate in the presence of stannous octoate catalyst. Polymers with lower plateau moduli exhibit faster rates of relaxation. Reactions of model urethanes suggest that exchange occurs through the tin-mediated exchange of the urethanes that does not require free hydroxyl groups. Furthermore, samples were incapable of elevated-temperature dissolution in a low-polarity solvent (1,2,4-trichlorobenzene) but readily dissolved in a high-polarity aprotic solvent (DMSO, 24 to 48 h). These findings indicate that urethane linkages, which are straightforward to incorporate, impart dynamic character to polymer networks of diverse chemical composition, likely through a urethane reversion mechanism.